TINJAUAN PENOMORAN GANDA REKAM MEDIS DI RS. BMC MAYAPADA BOGOR - Avif Abdul Aziz,; Irda Sari, (Journal of Innovation Research and Knowledge, 2021)
The hospital is one of the health service providers that organizes medical records. Medical records are used to document the patient's identity and all actions that have been given by health workers to patients. Medical record documents must be stored so that they can be useful for service continuity. The process of storing medical records refers to the numbering system that is obtained when the patient first registers. Errors in numbering can result in double numbering of the patient's medical record so that the impact on service delivery is hampered and the contents of the patient's medical record file are not sustainable. The purpose of this study was to determine the factors causing the double numbering of medical records, this study used a qualitative type of research, carried out by interviewing the registration officer. Data analysis used interview guidelines, observation guidelines and primary data. Duplicate numbering at the time of patient registration where patients get multiple numbers, and every month about 1-10 patients get double numbers. Educational qualifications, knowledge, and experience are less thorough and do not know about the medical record numbering system. There is still duplication of medical record numbering and for officers it is necessary to train and increase broad knowledge. It is hoped that the hospital can pay attention to the registration officer in providing medical record numbering.